Between local and global: The place of comparative philosophy through Heidegger and Daoism - BURIK, Steven (Institutional Knowledge at Singapore Management University, 2019)
It is often argued that comparative philosophy is afflicted by an inherent contradiction. For in order to be truly comparative, it needs to assume some over arching position with regard to the thinkers or thoughts under comparison, to somehow stand above or beyond what is being compared. In other words, it must transcend the things under comparison. If the comparative philosopher does not undertake at least the transcendence of her own culture, then she is in danger of imposing her own standards on foreign ways of thought.